Evaluation of Various Combination of Insecticidal Seed Treatments and Biopesticides Foliar Application against Aphid Infesting Coriander - Barad, A. H.; Prajapati, H. N.; Trivedi, N. P.; Dodiya, R. D. (International Journal of Bio-resource and Stress Management, 2025)
The field experiment was carried at Horticulture Farm, College of Horticulture, Anand Agricultural University, Anand during rabi, (November–February, 2019–20 and November–February, 2020–21) following randomized block design (factorial) with three replications and twelve different treatments. Present need in agriculture is not only getting higher production but also safety to environment and pollinators along with the management of insect-pests. Coriander is one of the important spices grown in India of which green leaves are utilised for culinary purpose and seeds in almost all Indian foods as an essential spice. A soft-bodied insect-pest, aphid infests the crop during its vegetative stage and umbel formation sucking cell-sap from tender shoots as well as seeds ultimately reducing their quality affecting yield. Insecticidal sprays have become very essential and frequent to mitigate aphids which also prove extremely harmful to flower visiting pollinators. With a view to reduce the load and dependency on chemical insecticides along with encouraging a healthy and safe agricultural ecosystem for pollinators and human beings, current experiment was formulated to test different chemical insecticides as seed treatments and biopesticides as foliar sprays as well as their combinations. The results show that use of chemical insecticide, imidacloprid 48 FS as seed treatment along with two foliar applications of Lecanicillium lecanii 1.15 WP can be effective in management of aphids as well as getting higher return in coriander.